Magnetic states of MnP: muon-spin rotation studies. (21st March 2017) - Khasanov, R; Amato, A; Bonfà, P; Guguchia, Z; Luetkens, H; Morenzoni, E; De Renzi, R; Zhigadlo, N D
Abstract: Muon-spin rotation data collected at ambient pressure ( p ) and at p = 2.42 GPa in MnP were analyzed to check their consistency with various low- and high-pressure magnetic structures reported in the literature. Our analysis confirms that in MnP the low-temperature and low-pressure helimagnetic phase is characterised by an increased value of the average magnetic moment compared to the high-temperature ferromagnetic phase. An elliptical double-helical structure with a propagation vector Q = ( 0, 0, 0.117 ), an a -axis moment elongated by approximately 18% and an additional tilt of the rotation plane towards c -direction by ≃ 4 –8° leads to a good agreement between the theory and the experiment. The analysis of the high-pressure μ SR data reveals that the new magnetic order appearing for pressures exceeding 1.5 GPa can not be described by keeping the propagation vector Q ∥ c . Even the extreme case—decoupling the double-helical structure into four individual helices—remains inconsistent with the experiment. It is shown that the high-pressure magnetic phase which is a precursor of superconductivity is an incommensurate helical state with Q ∥ b .